Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2010
DOI: 10.1038/jhh.2010.18
|View full text |Cite
|
Sign up to set email alerts
|

Regular slow-breathing exercise effects on blood pressure and breathing patterns at rest

Abstract: Previous studies reported that a device-guided slowbreathing (DGB) exercise decreases resting blood pressure (BP) in hypertensive patients. This study investigated the effects of daily practice of DGB on (a) 24-h BP and breathing patterns in the natural environment, as well as (b) BP and breathing pattern during clinic rest. Altogether, 40 participants with pre-hypertension or stage 1 hypertension were trained to decrease breathing rate through DGB or to passively attend to breathing (control, CTL) during dail… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
33
1
3

Year Published

2011
2011
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(45 citation statements)
references
References 22 publications
8
33
1
3
Order By: Relevance
“…In our study, long-term SLOWB exercise reduced office BP, whereas 24-h BP profile was not affected by this intervention. Our results are consistent with a recently published study evaluating the effects of daily practice device-guided SLOWB on BP in 40 participants with prehypertension or stage 1 hypertension, wherein 4 weeks of SLOWB training decreased clinic BP without changes in 24-h profile [35]. Previous studies demonstrated conflicting results regarding the effects of device-guided breathing on BP, with some studies reporting no significant difference in BP changes when hypertensive individuals with [36] or without [37] type 2 diabetes were randomized to SLOWB exercise or to listening to music through a Discman, whereas other studies reported a substantial reduction in BP in diabetic hypertensive individuals [38] as compared to a control group.…”
Section: Discussionsupporting
confidence: 95%
“…In our study, long-term SLOWB exercise reduced office BP, whereas 24-h BP profile was not affected by this intervention. Our results are consistent with a recently published study evaluating the effects of daily practice device-guided SLOWB on BP in 40 participants with prehypertension or stage 1 hypertension, wherein 4 weeks of SLOWB training decreased clinic BP without changes in 24-h profile [35]. Previous studies demonstrated conflicting results regarding the effects of device-guided breathing on BP, with some studies reporting no significant difference in BP changes when hypertensive individuals with [36] or without [37] type 2 diabetes were randomized to SLOWB exercise or to listening to music through a Discman, whereas other studies reported a substantial reduction in BP in diabetic hypertensive individuals [38] as compared to a control group.…”
Section: Discussionsupporting
confidence: 95%
“…In a recent meta-analysis, transcendental meditation was reported to effectively lower blood pressure in patients with hypertension, whereas psychological approaches to stress management were deemed ineffective. 89 Intriguingly, the results of several studies indicate that device-guided, home-based training with slow, deep breathing can effectively reduce blood pressure in patients with hypertension, [90][91][92] although this has not been a universal finding. 93 These findings are particularly intriguing given the recent identification of an amplified bursting of SNA related to the respiratory cycle that appears to contribute to the progression and maintenance of hypertension in rats, 7 and the alterations in respiratory-sympathetic coupling recently reported in human hypertension.…”
Section: 65mentioning
confidence: 99%
“…Based on the phenomena that CPC at slow breathing rate can increase heart rate variability and improve arterial baroreflex sensitivity [15,19], breathing control techniques have been employed to improve cardiovascular autonomic balance and reduce BP [2,33]. An FDA (the Food and Drug Administration, USA) approved device, Resperate (InterCure Ltd, Lod, Israel), has been developed for the treatment of hypertension by PB technology [35].…”
Section: Introductionmentioning
confidence: 99%